((3^-6/7)*(4^-3/7)*(9^3/7)*(2^6/7))/(2^2+2^0+2^-2): indices
Answers
Answered by
2
Question :- Given above in image .
Solution :- Refer to image .
formula used :-
In first step :-
- (a^m)^n = (a)^(m * n)
- a^(-m) = 1/a^m
In second step :-
- a^m * a^n = a^(m + n)
- a^0 = 1
In third step :-
- Additive inverse .
In fourth step :-
- a^0 = 1 { so, 1 + 1 = 2 }
therefore,
→ Final answer = (8/21)
Learn more :-
(7sqrt(3))/(sqrt(10+sqrt(3)))-(2sqrt(5))/(sqrt(6)+sqrt(5))-(3sqrt(2))/(sqrt(5)+3sqrt(2))
brainly.in/question/32043164
if the positive square root of (√190 +√ 80) i multiplied by (√2-1) and the
product is raised to the power of four the re...
brainly.in/question/26618255
Attachments:
![](https://hi-static.z-dn.net/files/dcf/a81ccc7dec0bdf3ced33bf8cf21b7e82.jpg)
![](https://hi-static.z-dn.net/files/d0b/5640163b4d07bba9f465c8962479b584.jpg)
Similar questions